2021
DOI: 10.1007/s00401-021-02308-0
|View full text |Cite
|
Sign up to set email alerts
|

Aminopeptidase A contributes to biochemical, anatomical and cognitive defects in Alzheimer’s disease (AD) mouse model and is increased at early stage in sporadic AD brain

Abstract: One of the main components of senile plaques in Alzheimer’s disease (AD)-affected brain is the Aβ peptide species harboring a pyroglutamate at position three pE3-Aβ. Several studies indicated that pE3-Aβ is toxic, prone to aggregation and serves as a seed of Aβ aggregation. The cyclisation of the glutamate residue is produced by glutaminyl cyclase, the pharmacological and genetic reductions of which significantly alleviate AD-related anatomical lesions and cognitive defects in mice models. The cyclisation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…For example, N-truncated Aβ 5-X is mainly produced from the caspase-cleaved form of APP and not from full-length Aβ (Murayama et al, 2007 ). Another potential alternative may be the generation the Aβ4-x peptide, a sequential cleavage of full-length Aβ by aminopeptidase A, meprin-β or dipeptidyl-peptidases (Sevalle et al, 2009 ; Antonyan et al, 2018 ; Schlenzig et al, 2018 ; Valverde et al, 2021 ). At least theoretically, Aβ 4-x could be derived from Aβ 2-x or Aβ 3-x peptide ( Figure 1B ).…”
Section: Aβ 4-x Can Be Generated By Enzymatic Cleavagementioning
confidence: 99%
“…For example, N-truncated Aβ 5-X is mainly produced from the caspase-cleaved form of APP and not from full-length Aβ (Murayama et al, 2007 ). Another potential alternative may be the generation the Aβ4-x peptide, a sequential cleavage of full-length Aβ by aminopeptidase A, meprin-β or dipeptidyl-peptidases (Sevalle et al, 2009 ; Antonyan et al, 2018 ; Schlenzig et al, 2018 ; Valverde et al, 2021 ). At least theoretically, Aβ 4-x could be derived from Aβ 2-x or Aβ 3-x peptide ( Figure 1B ).…”
Section: Aβ 4-x Can Be Generated By Enzymatic Cleavagementioning
confidence: 99%
“…S2 C ). It is of importance to note that our recent study indicated that synthetic pE3-Aβ could indeed alter dendritic morphology and mimic that triggered by APPswe expression ( 33 ). Overall, this set of data indicates that DPP4 contributes to the morphological alterations affecting spines in an ex vivo AD model.…”
Section: Resultsmentioning
confidence: 97%
“…2 ) showing that APA inhibitors enhanced the recovery of cellular flAβ. Furthermore, our recent work showed that the APA inhibitor RB150 and short hairpinRNA directed towards APA both rescue dendritic morphology, lower pE3-Aβ–positive and Aβ-positive plaques and loads, and improve memory defects in 3xTgAD mice ( 33 ). Interestingly, APA and DPP4 inhibitor–induced potentiation of flAβ recovery was additive, indicating that the two enzymes independently target flAβ.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, inhibition of AP-A with RB150 (described below) restored the density of mushroom dendritic spines and reduced filopodia-like immature spines in hippocampal organotypic slices. Moreover, the work showed increased AP-A activity in early cases of AD [ 85 ]. As discussed earlier in this review, environmental risk factors for AD, such as cholesterol metabolites have been shown to alter AP-A and AP-N expression and correlated with decreased spatial memory in mice [ 24 ].…”
Section: Novel Ras Drugsmentioning
confidence: 99%
“…In rats, it showed BP reduction activity from 2 to 15 h post-administration [ 89 ]. As mentioned before in this work, the proven activity of firibastat for neurodegeneration is based on the inhibition of aminopeptidase activity over Aβ, which decreases the abundance of toxic Aβ species and its effect on neuronal physiology [ 85 ]. We have also mentioned that vasoconstriction and reduction of glymphatic flow could promote protein aggregation in the brain; therefore firibastat, through the activity of EC33 in the brain, could potentially improve these risk factors that influence cognition directly by lowering AP-A activity and AngIII levels.…”
Section: Novel Ras Drugsmentioning
confidence: 99%